Customer Intention to Commit Motor Insurance Fraud: A Literature Review - Mohd Yusof, Nurul Hidayah; Abd Razak, Ahmad Zainal Abidin (International Business Education Journal, 2018)
Fraud in insurance is becoming an interesting issue nowadays among researchers and parties involved in the industries. Increase in numbers of insurance claim leads to unstable and unpredictable operating profit suffered by insurance companies. These claims are believed to include both bogus and authentic claims. Thus, the aim of this study is to examine customers’ intentions in committing motor insurance fraud. The objective is to determine the relationship between individual attitude and subjective norms on intention to commit motor insurance fraud. The sample for this study will be teachers from selected schools in Petaling District, Selangor. Data from the respondents will be collected using questionnaires. Statistical Package for Social Science (SPSS) will be used to analyze the data collected. Specifically, correlation and regression will be used to test the hypothesis. Finding from this study is believed useful for insurance regulator and industry to handle insurance fraud attempts.